Utility of nintedanib for severe idiopathic pulmonary fibrosis: a single-center retrospective study [Letter] - Orsatti L; Fortea J; Quaresma M (Dove Medical Press, 2019)
Leticia Orsatti, Josep Fortea, Manuel Quaresma Boehringer Ingelheim International GmbH, Ingelheim, GermanyWe read with interest the study by Abe et al on the clinical utility of nintedanib in patients with severe idiopathic pulmonary fibrosis (IPF).1 Based on the retrospective follow-up of 51 patients, the authors concluded that the survival benefit from nintedanib is reduced among patients with severe IPF (n=17) compared with those with mild-to-moderate IPF (n=34), but that the prognosis for patients with severe IPF is significantly better in those who remain on nintedanib for more than 3 months.In our opinion, the study design does not allow conclusions to be drawn about the treatment effect of nintedanib on survival in patients with severe versus mild-tomoderate IPF.View the original paper by Abe and colleagues